Lipoprotein(a): An Independent Risk factor of Cardiovascular Disease (Central Medical College Journal, 2022)
Background: Cardiovascular disease is currently one of the most common causes of morbidity and mortality in developed and developing countries. Many traditional risk factors such as age, gender, smoking, diabetes mellitus, dyslipidemia and hypertension play an important role in the development of vascular disorders. Lipoprotein (a) or Lp (a), an intriguing lipoprotein particle is also considered to be an important risk factor for the development of cardiovascular disease. Lp(a) is a LDL-like molecule consisting of an apolipoprotein B-100 (apo B-100) particle attached by a disulphide bridge to a unique protein, apolipoprotein(a)/ apo(a) which distinguishes it from LDL. Many epidemiological studies have reported the positive associations of Lp(a) concentration with atherosclerosis, coronary artery disease and stroke.Central Medical College Journal Vol 5 No 1 Jan 2021 PP 51-58